Tanggapan Epilog Kitab Ayub 42:1-17 Terhadap Teologi Retribusi - Matulessy, Yosua Yosia; Saputro, Anon Dwi; Sumarmi, Ni Putu (Jurnal Teologi dan Pelayanan Kerusso, 2025)
Suffering is often regarded as a direct consequence of sin in theological tradition, but the story of Job challenges this view. The story of Job reflects the reversal of this understanding. The purpose of this research is to analyze the epilogue of the Book of Job as a response that can correct the misunderstanding of retributive theology regarding the suffering of the righteous. The view opposed in the epilogue is the belief that the righteous will surely be blessed and the sinners will surely suffer. This is rejected in the epilogue, which states that even the righteous can suffer. The method used is a qualitative method with a thematic approach. The author identifies three central themes in retributive theology: the emphasis on rationality-morality, misconceptions about the nature of God from ancestral traditions, and God's judgment. These themes will be examined in the epilogue of the Book of Job, with attention to exegetical study of the epilogue's narrative. The research findings show that the epilogue rejects the idea of retributive theology through three main components: God's acceptance (42:7-8), Job's prayer to God (42:9), and Job's restoration (42:10-17). The epilogue of the Book of Job rejects the concept of retributive theology through these three interconnected components, based on the reasoning that (1) the relationship between God and humans is dynamic, and (2) God's grace is the source of restoration.